PARETO-OPTIMAL REGION OF MASS-TRAJECTORY PARAMETERS OF TRANSFORMER AVIATION SYSTEM - Yurii K. Ziatdinov; Albert M. Voronin; Oleksandr Y. Permiakov; Ihor D. Varlamov (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The paper considers on the search optimal variants problem of transformer aviation systems construction. At the same time massively-trajectory parameters of the system are determined, which characterize the transformer with sufficient completeness and reliability and simultaneously reduce the dimensionality of the problem.